PENGEMBANGAN KOMIK SEBAGAI MEDIA PEMBELAJARAN IPA KELAS VIII SMP PADA MATERI POKOK SISTEM TRANSPORTASI - Muflikhatur Rohmah Rohmah; Wan Syafi’i syafi'i; Darmadi ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract : The purpose of this research are for design and develop of comic as media learning for science in 8th Junior High School. The research was conducted at Study Program of Biology Education campus FKIP University of Riau from April until Juni 2015. This research used Research and Development (R&D) approach with ADDIE model. The comic have subject is Transportation System. We used validation sheet were filled by 5 validators. Then, we executed of limited trial at 10 students in 8th grade Junior High School 1 Pekanbaru with student questionnaire responses. The value of media comic validation can be seen at 5 aspects, they are simplicity, suppression, balance, integration and comic design. The result is media comic can aplication in learning activity at class Key Word : Comic, Media Learning for Science, Transportation System